Analysis of Museum Website Requirements Based on AISAS Model - Hadiapurwa, Angga; Nugraha, Hafsah; Syafitri, Nanda Khaerunnisa (Edulib, 2021)
Regarding promotional activities, almost all museums in Bandung use social media as a means of promoting the existence and activities of their museums. The results of the analysis of website ownership show that five of the eleven museums in the city of Bandung do not or do not have a website. Museum as an open institution frees the public to access information owned by the museum and as a source of information, museums need to think about how the information they have can be accessed and utilized by the public. To determine the types of information needs about a promotion that is needed by the community, an analysis is needed related to the elements that must be owned in promotional activities, namely attention, interest, search, action, and share which are then shortened to AISAS. This study uses descriptive analysis with data collection using questionnaires and interviews. The research participants consisted of the general public and the head of the museum. The results showed that the most sought-after information was promotional information related to elements (1) search, (2) attention, (3) interest, (4) action, and (5) share, with the type of promotional information related to location. museums, museum opening hours, interesting promotional content, and also the presence of multimedia content. The analysis process involving the head of the museum also provides additional information in the form of the availability of supporting technology and the availability of human resources which adds to the fact that content in promotional activity is not everything.